Multiple Extrauterine Adenomyomas Presenting in Upper Abdomen and Pelvis: A Case Report and Brief Review of the Literature - Mana Moghadamfalahi; Daniel S. Metzinger (Case Reports in Obstetrics and Gynecology)
Adenomyomas are benign tumors composed of smooth muscle and endometrial tissue. These tumors usually arise from the myometrium. Extrauterine adenomyomas are rare with only a few case reports available in the literature. Here, we report an unusual case of multiple adenomyomas in a 39-year-old woman six years after hysterectomy for multiple leiomyomata. To the best of our knowledge, this is the first case of extrauterine adenomyoma presenting as an upper abdominal mass.